The Impact Analysis of Fear of Missing Out (FoMO) and You Only Live Once (YOLO) on Intention to use Online Lending in Pesantren Students - Yudi, Rahma; Suyanto; Mohamamd Zaenal Abidin; Abdillah Hanif Fathurrahman (University of Darussalam Gontor, 2024)
The disorganized lifestyle of today's Z generation (Gen Z) has an impact on financial literacy. This condition ends up in squandering money and even using online lending just for fun. Nevertheless, pesantren students have their mindset and lifestyle to protect themselves from things that do not reflect a Muslim youth. The purpose of this study is to analyse the impact of fear of Missing Out (FoMO) and You Only Live Once (YOLO) on the intention to use online lending among pesantren students. This research includes quantitative research, which uses secondary data obtained directly from researchers from the main data source. The Eviews 12 application was used to test multiple linear statistical methods. The student population obtained was 686 registered as active students from semesters 4-8. The sample used from the total population of 259 students. The results of this study show that FoMO, and YOLO variables affect simultaneously the intention to use online lending. The partial test in this study proves that the FoMO variable has a significant effect on intention to use online lending. This is an indicator that the higher the FoMO, the higher the intention to use online lending. However, a pesantren student must control FoMO so that it does not lead one to make online lending. While YOLO has no effect, this shows that pesantren-based education can make students' lives have a positive purpose in life in the world. This study found that FoMO and YOLO have a role in the Gen Z finances that lead them to use online lending, this study also suggests paying more attention to the Gen Z lifestyle in order to avoid online loan arrears that can be detrimental to the future, especially for Muslim students.